2021
DOI: 10.1055/s-0041-1723751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mediterranean Diet in Patients with Nonalcoholic Fatty Liver Disease: A Systematic Review, Meta-Analysis, and Meta-Regression Analysis of Randomized Controlled Trials

Abstract: We conducted a meta-analysis to investigate the effects of the Mediterranean Diet (Med-Diet) on hepatic steatosis and insulin resistance in patients with nonalcoholic fatty liver disease (NAFLD). Six randomized controlled trials were selected for the meta-analysis (sample size: 250 participants). In the meta-analysis, there was no significant difference in body mass index and waist circumference between the Med-Diet and control groups. Med-Diet significantly reduced fatty liver index (FLI) compared with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 46 publications
3
33
0
2
Order By: Relevance
“…There was consistent evidence that MD interventions improved one or more measures of NAFLD activity and meta-analysis showed a significant effect on post-intervention ALT, FLI and LSM. This is consistent with recent reviews which concluded that MD interventions improved FLI [56], liver enzymes and NAFLD severity indices [57]. Very limited evidence suggested that individual components of MD such as wholegrains and olive oil may improve NAFLD surrogate markers [43e45], but meta-analysis revealed no significant effects.…”
Section: The Effectiveness Of MD and Md Component Interventionssupporting
confidence: 89%
“…There was consistent evidence that MD interventions improved one or more measures of NAFLD activity and meta-analysis showed a significant effect on post-intervention ALT, FLI and LSM. This is consistent with recent reviews which concluded that MD interventions improved FLI [56], liver enzymes and NAFLD severity indices [57]. Very limited evidence suggested that individual components of MD such as wholegrains and olive oil may improve NAFLD surrogate markers [43e45], but meta-analysis revealed no significant effects.…”
Section: The Effectiveness Of MD and Md Component Interventionssupporting
confidence: 89%
“…The Mediterranean diet significantly reduced the fatty liver index (standardized mean difference, -1.06; CI, -1.95 to -0.17; P = 0.02), as well as the homeostasis model assessment of insulin resistance (standardized mean difference, -0.34; CI, -0.65 to -0.03; P = 0.03). 27 Another recent study compared the Mediterranean diet versus a "green-rich" Mediterranean diet to see the effect on hepatic fat. 28 The "green" group consumed green tea, Mankai, and a "green" shake on top of the typical isocaloric Mediterranean diet.…”
Section: Role Of Specific Diets In Nafldmentioning
confidence: 99%
“…Interventional studies showed that consuming MD was associated with an improvement in liver enzymes, steatosis, liver stiffness, and lipid profile, even without weight loss [218][219][220][221][222][223][224][225][226][227] . We still need long-term trials to understand the role of MD on liver histopathology.…”
Section: Eating Patterns and Mafldmentioning
confidence: 99%